Evaluation of the Behaviors of Physicians Working in Primary Healthcare Institutions About Secondhand Smoke - Karaçorlu, Fatma Nur; Pirinçci, Edibe (Addicta: The Turkish Journal on Addictions, 2023)
The aim of this study was to evaluate the behaviors of physicians working in primary healthcare institutions in Elazığ province about secondhand smoke. This cross-sectional study was conducted on 250 physicians working in primary healthcare institutions in Elazığ. For data collection, a questionnaire was used. Obtained data were evaluated with frequency, percentage, mean ± standard deviation, chi-square, Mann– Whitney U-test, and binary logistic regression analysis. The mean age of the physicians was 40.86 ± 10.58 years and 68.0% of them were male. Of the physicians, 12% received training on secondhand smoke, 13.2% asked patients about secondhand smoke exposure, and 34.8% advised that patients be protected from secondhand smoke exposure. Male physicians (odds ratio: 3.00, 95% Confidence Interval: 1.10–8.18) and physicians trained in secondhand smoke (odds ratio: 3.55, 95% Confidence Interval: 1.44–8.78) stated that they asked patients more frequently about their exposure to secondhand smoke. As a result, very few of the primary care physicians ask about the exposure of their patients to secondhand smoke and very few of them have received training on secondhand smoke. The number of trained physicians should be increased in order for physicians to ask patients about secondhand smoke exposure and to provide counseling on this issue.